2021
DOI: 10.3390/cells10113224
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance and Advantages of Intradermal Test Results in 371 Patients with Allergic Rhinitis, Asthma and/or Otitis Media with Effusion

Abstract: Background: We evaluated the value of positive intradermal dilution testing (IDT) after negative skin prick tests (SPT) by retrospectively determining allergy immunotherapy (AIT) outcomes. Methods: This private practice, cohort study compared the relative value of SPT vs. IDT in 371 adults and children with suspected manifestations of allergy: chronic allergic rhinitis (AR), asthma and/or chronic otitis media with effusion (OME). The primary outcome measure was symptom resolution following immunotherapy, as de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
(135 reference statements)
0
7
0
Order By: Relevance
“…Histologic, epidemiologic, and clinical studies based on objective allergy testing 6 have, firstly, established that the majority of OME patients are atopic and, secondly, demonstrated that all the mediators necessary for a Th 2 allergic response are present in the middle ear. 5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histologic, epidemiologic, and clinical studies based on objective allergy testing 6 have, firstly, established that the majority of OME patients are atopic and, secondly, demonstrated that all the mediators necessary for a Th 2 allergic response are present in the middle ear. 5…”
Section: Discussionmentioning
confidence: 99%
“…( P = .28 = NS) 5 As stated: “the concept of the “unified airway” closely links IgE-mediated hypersensitivity with allergic rhinitis/chronic sinusitis, asthma, and otitis media with effusion.” In only 29% of the 118 with OME was ear disease the sole manifestation of their allergy. 6 Table 4…”
Section: Methodsmentioning
confidence: 99%
“…Changes in skin prick test (SPT) have a high degree of diagnostic performance in the evaluation of efficacy in HDM-SCIT according to tIgE levels [ 111 ]. Recently, one study reported the increased sensitivity and clinical relevance of the intradermal test compared to SPT to predict AIT effectiveness in respiratory allergic diseases [ 115 ]. Hoshino et al [ 116 ] report an interesting finding where the proportion of responders to AIT had high periostin and high fractional exhaled nitric oxide levels, which opens a window to explore the combination of in vivo and in vitro biomarkers.…”
Section: Predictive Biomarkers For Ait Outcomes In Allergic Diseasesmentioning
confidence: 99%
“…According to the guidelines on allergy diagnosis the performance of intradermal tests (IDT) is currently limited for the assessment of venom hypersensitivity. An article describing the use of IDT for the diagnosis of allergic rhinitis, asthma and/or chronic otitis media with effusion (OME) is published in this issue [ 10 ]. It suggests that patients are underdiagnosed with SPT only and that decisions on AIT should include the results of IDT.…”
mentioning
confidence: 99%
“…It suggests that patients are underdiagnosed with SPT only and that decisions on AIT should include the results of IDT. The efficacy of AIT in patients with low allergen-sensitivity (SPT negative/IDT positive) was found to be similar to the relevant one in patients with high allergen-sensitivity (SPT+IDT positive) [ 10 ]. Authors support that the performance of IDT should be assessed in order to detect “allergens clinically relevant to diagnosis of AIT-responsive atopic disease” [ 10 ].…”
mentioning
confidence: 99%